Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Materi Kelangkaan sebagai Permasalahan Ekonomi melalui Model Student Teams Achievement Division di Kelas VII.10 SMP Negeri 1 Cileungsi Kabupaten Bogor Tahun 2017/2018 - Levi Olivia Tunita (JURNAL KAJIAN ISLAM MODERN, 2021)
The research is motivated by students who are less interested, less active, and tend not to be creative. This is indicated by a less enthusiastic attitude when the lesson takes place which causes low scores on the Social Sciences (IPS) test results for students, because teachers still use learning models that do not stimulate students to study harder. The purpose of carrying out this research is to find out the increase in social studies learning outcomes for students in class Vll-10 SMP Negeri 1 Cileungsi semester 2 for the 2017/2018 academic year on material scarcity as an economic problem through cooperative learning with the Student Teams Achievement Division (STAD) model. This research is a classroom action research with the research subjects of class VII-10 students. The research location is SMP Negeri 1 Cileungsi in semester 2 of the 2017/2018 academic year. In this study consisted of two cycles. Where in each cycle consists of planning, action, observation, evaluation and reflection. Data collection through observation and tests. Data collection techniques in this study in addition to using observation also use direct assessment. The results obtained are that through cooperative learning the STAD model is able to make a positive contribution to activities in group discussions and to improve social studies learning outcomes. This is evident from the increase in activity in group discussions in the first cycle of 57.90%, the second cycle of 82.46 and social studies learning outcomes which at the time, the first cycle of 69.47% and the second cycle of 80.53%.